Electronic materials and processes handbook - Harper, Charles A. (McGraw-Hill, 2003)
A revised, updated and expanded reference (the first edition of 1970 was titled Handbook of Materials and Processes for Electronics) on electronic materials and process technology, presenting a source book of practical material data, guidelines, information and manufacturing methods including cost and fabrication trade-off, design and application criteria, and performance limits. Annotation c. by Book News, Inc., Portland, Or.